Task-based Approach to Teaching English for Tour Guiding Students in EFL Context - Gusti Astika (TEFLIN Journal: A publication on the teaching and learning of English, 2000)
Abstract: This paper describes a task-based approach to teaching EnÃÂglish using an authentic material obtained from a guided tour. It begins with a brief discussion on forms-focused instruction, then follows a disÃÂcussion on meaning-focused and form-focused instruction. This paper also cites theoretical framework and research to justify the implementaÃÂtion of task-based language teaching. It argues that task-based language teaching needs to be modified to accommodate the needs of teaching the language in EFL contexts. At the end of the paper, a procedure is pro-posed for the implementation of task-based language teaching using a sample material from tour guiding.